Dynamic covalent chemistry (DCC) in dental restorative materials: Implementation of a DCC-based adaptive interface (AI) at the resin–filler interface for improved performance. Issue 1 (January 2020) - Sowan, Nancy; Dobson, Adam; Podgorski, Maciej; Bowman, Christopher N.
Abstract: Objective: Dental restorative composites have been extensively studied with a goal to improve material performance. However, stress induced microcracks from polymerization shrinkage, thermal and other stresses along with the low fracture toughness of methacrylate-based composites remain significant problems. Herein, the study focuses on applying a dynamic covalent chemistry (DCC)-based adaptive interface to conventional BisGMA/TEGDMA (70:30) dental resins by coupling moieties capable of thiol–thioester (TTE) DCC to the resin–filler interface as a means to induce interfacial stress relaxation and promote interfacial healing. Methods: Silica nanoparticles (SNP) are functionalized with TTE-functionalized silanes to covalently bond the interface to the network while simultaneously facilitating relaxation of the filler–matrix interface via DCC. The functionalized particles were incorporated into the otherwise static conventional BisGMA/TEGDMA (70:30) dental resins. The role of interfacial bond exchange to enhance dental composite performance in response to shrinkage and other stresses, flexural modulus and toughness was investigated. Shrinkage stress was monitored with a tensometer coupled with FTIR spectroscopy. Flexural modulus/strength and flexural toughness were characterized in three-point bending on a universal testing machine. Results: A reduction of 30% in shrinkage stress was achieved when interfacial TTE bond exchange was activated while not only maintaining but also enhancing mechanical properties of the composite. These enhancements include a 60% increase in Young's modulus, 33% increase in flexural strength and 35% increase in the toughness, relative to composites unable to undergo DCC but otherwise identical in composition. Furthermore, by combining interfacial DCC with resin-based DCC, an 80% reduction of shrinkage-induced stress is observed in a thiol–ene system "equipped" with both types of DCC mechanisms relative to the composite without DCC in either the resin or at the resin–filler interface. Significance: This behavior highlights the advantages of utilizing the DCC at the resin–filler interface as a stress-relieving mechanism that is compatible with current and future developments in the field of dental restorative materials, nearly independent of the type of resin improvements and types that will be used, as it can dramatically enhance their mechanical performance by reducing both polymerization and mechanically applied stresses throughout the composite lifetime.